Qualitative Landslide Susceptibility Assessment in Small Areas. (2016) - Mandaglio, Maria Clorinda; Gioffrè, Domenico; Pitasi, Antonia; Moraci, Nicola
Abstract: The paper shows the application of heuristic methods to assess qualitatively the landslides susceptibility of an area located at the end of the flowslides path. Numerical analyses have been performed to study the flowslide propagation phase and landslides susceptibility maps of the studied area have been obtained. Focusing the attention on a zone located at the end of the flowslides path, qualitative susceptibility analyses have been applied using two heuristic methods. The comparison of obtained results highlighted how heuristic methods strongly depend on the judgement of the person carrying out the analysis.